Elastic wave propagation in anisotropic polycrystals: inferring physical properties of glacier ice. (21st December 2022) - Rathmann, Nicholas M.; Grinsted, Aslak; Mosegaard, Klaus; Lilien, David A.; Westhoff, Julien; Hvidberg, Christine S.; Prior, David J.; Lutz, Franz; Thomas, Rilee E.; Dahl-Jensen, Dorthe
Abstract : An optimization problem is proposed for inferring physical properties of polycrystals given ultrasonic (elastic) wave velocity measurements, made across multiple sample orientations. The feasibility of the method is demonstrated by inferring both the effective grain elastic parameters and the grain c -axis orientation distribution function (ODF) of ice-core samples from Priestley glacier, Antarctica. The method relies on expanding the ODF in terms of a spherical harmonic series, which allows for a non-parametric estimation of the sample ODF. Moreover, any linear combination of the Voigt (strain) and Reuss (stress) homogenization scheme is allowed, although for glacier ice, the exact choice is found to matter little for bulk elastic behaviour, and thus for inferred physical properties, too. Finally, the accuracy of the inferred grain elastic parameters is discussed, including the well-posedness and shortcomings of the inverse problem, relevant for future adoptions in glaciology, geology and elsewhere.